Effectiveness of shifting traditional lecture to interactive lecture to teach nursing students - Afrasiabifar, Ardashir; Asadolah, Mosavi (Investigación y Educación en Enfermería, 2019)
Objective. This study was conducted to examine effectiveness of interactive lecture in teaching nursing students compared to traditional lecture. Methods. This study is a quasi-experimental design in which 29 students participated in eighteen sessions of intensive nursing care in Yasuj University of Medical Sciences, Iran. These sessions were randomly allocated for the interactive lecture and the traditional lecture. The interactive lecture consists in this steps: explaining the learning objectives, taking the pre-test, teaching the subjects of each session, Group discussion with introduction of the clinical cases, answering students’ questions and mutual feedbacks, taking the post-test, and introducing students’ future activities. The effectiveness of applied teaching method was evaluated through pre-test, post-test of each session, mid-term and final exams. Results. Significant statistical differences were observed in terms of students' mean score (p=0.001) and their satisfaction (p=0.001) in the interactive teaching method compared to traditional lectures. Further preparation, active participation and received immediate feedback were some benefits reported for the interactive teaching method. Conclusion. The interactive lecture resulted in significant learning and furthers nursing students’ active participation in the teaching-learning process. How to cite this article: Afrasiabifar A, Asadolah M. Effectiveness of shifting traditional lecture to interactive lecture to teach nursing students. Invest. Educ. Enferm. 2019; 37(1):e07.